ChemInform Abstract: Enantioselective Imine Reduction Catalyzed by Imine Reductases and Artificial Metalloenzymes. Issue 27 (8th July 2014) - Gamenara, Daniela; Dominguez de Maria, Pablo
Abstract Review: [25 refs.